Investigations of initial particle stages during spark discharge. (22nd July 2015) - Ludvigsson, Linus; Meuller, Bengt O; Messing, Maria E
Abstract: The number of nanoparticle-based products on the market is expected to increase considerably during the coming decades. This forces the industry to have highly meticulous manufacturing of large amounts of nanoparticles using cheap and environmentally friendly methods. For the production of metal nanoparticles spark discharge generation is a promising route to fulfill these demands. The spark discharge generator can be easily scaled-up for mass production due to its simple design solely by placing several units in parallel. Before doing so, one first needs to optimize a single spark discharge generator unit. To optimize the spark discharge generator in a controlled way the first stage of nanoparticle formation needs to be understood. To improve this understanding we have constructed a customized nanoparticle sampler to enable sampling of the initial stages of particle formation for imaging in a TEM. In this article we present the design of the sampler and discuss optimal sampling parameters. We also present how the generation parameters can be tuned in order to affect the first stages of particle formation and hence the final nanoparticles.